2017
DOI: 10.4142/jvs.2017.18.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of marbofloxacin in pigs after a single intramuscular injection

Abstract: Tissue distribution of marbofloxacin was studied in pigs after a single intramuscular injection at 2.5 mg/kg body weight. Samples of plasma, muscle, liver, kidney, heart, lung, and muscle at the injection site were randomly collected from five pigs at 2, 6, 10, 24, 48, 72, and 96 h after administration. Marbofloxacin concentrations were determined by using high-performance liquid chromatography with ultraviolet detection and were subjected to non-compartmental analysis to obtain kinetic parameters. The elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 20 publications
2
18
2
Order By: Relevance
“…The results obtained in the present study confirmed that the absorption and distribution of marbofloxacin administered to rabbits via intramuscular injection reach high levels in a short time in kidney, liver, lung and muscle which were in agreement with the previous reports [10, 16,17,19]. Marbofloxacin remained within the detectable limit till the 5 th day in most tested tissues, while in kidney it remained till the 7 th day following last administration of the drug.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results obtained in the present study confirmed that the absorption and distribution of marbofloxacin administered to rabbits via intramuscular injection reach high levels in a short time in kidney, liver, lung and muscle which were in agreement with the previous reports [10, 16,17,19]. Marbofloxacin remained within the detectable limit till the 5 th day in most tested tissues, while in kidney it remained till the 7 th day following last administration of the drug.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in agreement with Ding et al [10] and Anadon et al [16] who reported that marbofloxacin concentration in kidney was more than that in liver. But is contrast with Ligabue et al [17] and Yang et al [19] who reported that marbofloxacin concentration in liver was more than that in kidney.…”
Section: Discussioncontrasting
confidence: 51%
“…MBF is distributed widely throughout the animals’ bodies, which could reach 1.6 times higher drug concentrations in the skin than in the plasma in dogs, and MBF concentrations in the plasma can remain above the MIC (>24 h) longer than the dose density ( Cester et al, 1996 ; Schneider et al, 1996 ). Although some studies have reported the pharmacokinetics of MBF in animals including pigs ( Ding et al, 2010 ; Schneider et al, 2014 ; Yang et al, 2016 ), the pharmacokinetic data of MBF in pigs plasma and intestinal content are not sufficient enough to precisely predict the efficacy of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…literature (Ding et al, 2010;Schneider et al, 2014;Yang et al, 2017). As shown in Table 1, Cmax increased in a dose dependent manner.…”
Section: Resultsmentioning
confidence: 77%
“…Marbofloxacin is a synthetic third-generation fluoroquinolone with a broad spectrum of activity, licensed only for animals. It is particularly indicated to treat respiratory infections, metritis-mastitis-agalactia syndrome, and to treat skin and soft tissue infections in animals (Yang et al, 2017). Fluoroquinolones are concentration dependent antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%